PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN SPEAKING SISWA - Nasyatul Aisyah (UNIB Press, 2021)
The purpose of this study was to describe the application of role playing learning models in improving students' speaking. The design of this study is classroom action research consisting of three cycles. each cycle consists of planning, action, observation, and reflection. Respondents in this study were 25 students consisting of 10 men and 15 women. Data collection uses observation sheets with 6 aspects assessed, namely: pronunciation, grammar, vocabulary, fluency, content of speech and understanding. The data analysis used is mean and inductive. The results showed that the application of role playing learning models can improve students' speaking